An Analysis of Fisher’s Theory of Spiritual Well-Being from al-Ghazali’s Perspective - Warlan Sukandar (Program Studi Bimbingan Konseling, Fakultas Tarbiyah dan Ilmu Keguruan UIN Bukittinggi, 2025)
Spiritual well-being is an essential dimension of human life that reflects the harmony of one's relationship with the self, others, the environment, and God. John W. Fisher developed a model of spiritual well-being comprising four relational domains, which has been widely applied in contemporary psychology and education. On the other hand, Imam al-Ghazali, through his classical work Kimiya as-Sa’adah (The Alchemy of Happiness), emphasized that spiritual well-being can only be achieved through the purification of the soul (tazkiyatun nafs) and drawing closer to Allah as the ultimate purpose of life. This study aims to analyze and compare Fisher’s theory of spiritual well-being from al-Ghazali’s perspective, in order to gain a deeper and more transformative understanding of human spirituality. Using a qualitative approach through library research, the study finds that although the two figures originate from different traditions and paradigms, both place the transcendent relationship at the core of spiritual happiness. Integrating these two approaches can enrich the development of spiritual well-being that is not only rational and measurable but also infused with spiritual values, making it highly relevant for education, counseling, and spiritual life in the modern.